Kampanye dalam Pemasaran Politik dan Brand Politik - Winda Kustiawan; Ahmad Farhan Ulya; M. Darma Marpaung; M. Imam Malik, M. Nadzim (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Political marketing is a permanent concept that must be carried out continuously by political candidates in building public trust and image. Marketing is needed to face competition in fighting for the market, which in this case is the voters. In the political marketing process, the application of the 4P of the marketing mix is used, namely product, price, promotion, and placement. This paper examines how campaigns are in political marketing and how political brands emerge. By using descriptive qualitative analysis, the researcher wants to analyze the data by properly describing the collected data related to campaigns in political marketing and political brands.